2014
DOI: 10.1016/j.bone.2014.01.004
|View full text |Cite
|
Sign up to set email alerts
|

Microgravity control of autophagy modulates osteoclastogenesis

Abstract: Evidence indicates that astronauts experience significant bone loss during space mission. Recently, we used the NASA developed rotary cell culture system (RCCS) to simulate microgravity (μXg) conditions and demonstrated increased osteoclastogenesis in mouse bone marrow cultures. Autophagy is a cellular recycling process of nutrients. Therefore, we hypothesize that μXg control of autophagy modulates osteoclastogenesis. Real-time PCR analysis of total RNA isolated from mouse bone marrow derived non-adherent cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
78
0
2

Year Published

2014
2014
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 82 publications
(81 citation statements)
references
References 44 publications
1
78
0
2
Order By: Relevance
“…The vessel was filled with Dulbecco's Modified Eagle Medium (DMEM) free of bubbles and rotated at a constant speed of 16 rpm for 24 h to simulate microgravity (0.008 Xg), termed µXg. Ground based cultures were considered as control gravity (Xg) …”
Section: Methodsmentioning
confidence: 99%
“…The vessel was filled with Dulbecco's Modified Eagle Medium (DMEM) free of bubbles and rotated at a constant speed of 16 rpm for 24 h to simulate microgravity (0.008 Xg), termed µXg. Ground based cultures were considered as control gravity (Xg) …”
Section: Methodsmentioning
confidence: 99%
“…When cultured in 1 g, cells previously exposed to microgravity display an increased mesenchymal and hematopoietic differentiation, suggesting that microgravity causes an accumulation of undifferentiated precursors (Blaber et al, 2014). A role for the autophagic control of osteoclastogenesis in response to microgravity has been proposed for mouse bone (Sambandam et al, 2014). A recent review by Ulbrich et al (2014) details the impact of simulated and real microgravity on bone and mesenchymal cells and their osteogenic potential.…”
Section: Microgravity Adult Stem Cells and Tissue Renewalmentioning
confidence: 99%
“…Autophagy is a dynamic catabolic process that delivers cellular components to the lysosome for degradation to retrieve molecules and regain energy to maintain cellular homeostasis [24,25]. Recently, reports have shown that the upregulation of autophagy contributes to osteoclastogenesis in response to hypoxic conditions, oxidative stress and microgravity in vitro [5,26,27]. However, the role of autophagy in osteoclast formation and function with glucocorticoid exposure remains unclear.…”
Section: Introductionmentioning
confidence: 97%